PROBLEMATIKA EKOLOGI DALAM NOVEL SUMI KARYA JAZULI IMAM (KAJIAN EKOKRITIK SASTRA) - Bayu Suta; Samsu Somadayo; Heru Kurniawan (Madah: Jurnal Bahasa dan Sastra, 2022)
Environmental and natural phenomena are hotly discussed issues in the latest development period. Various means are used in the voice of the environmental crisis, one of which is in novels or literary works. This study aims to describe the ecological problems contained in the novel Sumi by Jazuli Imam. The method applied to the research is descriptive qualitative. The source of the data used is the novel Sumi by Jazuli Imam with the data used are parts of the novel in the form of story quotes and also character dialogues. In this study, the data was analyzed by conducting content analysis techniques, data acquisition was carried out by means of listening techniques and note-taking techniques.  The results found in this study are ethical studies of environmental wisdom, having moral aspects in the form of respect for nature, moral responsibility for nature, and the principle of affection and concern for nature. These elements are depicted through a series of events starting from (1) tree care, (2) forest destruction (deforestation), and (3) ecosystem conditions.